(untitled) (Research, Society and Development, 2022)
Objective: to analyze the spirituality and religiosity of the elderly who participate in a Living Group (GC), in the municipality of Catalão, Goiás, and their meanings, in times of adversity, especially in the COVID-19 pandemic period. Method: Descriptive, exploratory study, with a qualitative approach, carried out with 8 elderly members of a CG. Data collection was carried out through calls and video calls, via cell phone application, using the Duke Religiosity Index and Pinto and Pais-Ribeiro spirituality scales. Bardin’s categorical thematic content analysis was used as a data analysis method. Results: Two major categories were structured: 1) Meaning of faith, religiosity and spirituality in the lives of the elderly and 2) The importance of the religious and spiritual dimension in times of pandemic and their meanings. Conclusion: the religious and spiritual dimensions are important elements that offer positive feelings and help in coping with stressful situations.